GEJALA RUBELA BAWAAN (KONGENITAL) BERDASARKAN PEMERIKSAAN SEROLOGIS DAN RNA VIRUS - Kadek Kadek; S. Darmadi (Indonesian Association of Clinical Pathologist and Medical laboratory, 2007)
Rubella infection with occurs during pregnancy, especially during the first trimester often caused by Congenital Rubella Syndrome(CRS). CRS can resulting abortions, miscarriages, stillbirth, and severe birth defects. The baby diagnosed with CRS when characterizedby signs or symptoms from the following two categories A (Cataracts/congenital glaucoma, congenital heart disease (most commonlypatent ductus arteriosus or peripheral pulmonary artery stenosis), loss of hearing, pigmentary retinopathy) or one categorie A andone catagorie B (Purpura, splenomegaly, jaundice, microencephaly, mental retardation, meningoencephalitis, radiolucent bone disease.Laboratory confirmation can be obtained by any of the following: virus isolation, serologi test (pasif hemaglutination, latex agglutinationtest, hemaglutination inhibisi, Flouresence immunoassay, Enzyme immunoassay), RNA test.